To history of floristic search of the Askanian steppe in XIX–XXІ century: inventory results and critical comments (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Detailed description of inventories of vascular flora of the Ascanian steppe during XIX–XX centuries and results of original researches in 2003–2010 are given in the paper. The results of all floristic inventories are collected firstly into a unified nomenclatural checklist with general taxonomic interpretation. According to analysis of previous floristic works, current observations and critical revision of herbarium collections, a synopsis of vascular flora of the core area of the Biosphere Reserve «Asсania Nova» includes 509 species whith 33 species recorded firstly. 73 species are excluded from the list, 26 species still have critical taxonomic status.
Keywords: Askanian steppe, flora of vascular plants, inventory results, critical analysis, nomenclatural and taxonomic redaction, current synopsis.